The Residual Patriarchy Ideology in Moana Disney Film by Ron Clements and John Musker: An Application of Elaine Showalter’s Feminist Criticism - Hartina Hamado (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2017)
This study is aimed to analyze Moana Disney movie in term of analytical of residual patriarchal ideology by using feminist criticism: women as a reader that produced by Elaine Showalter and found the hide messages including the stereotype and patriarchal system that is undiscovered by the men as the author of the workthat is Moana Disney movie. The method which is used in this study is the qualitative method and in descriptive form. The source of data that was obtained in this study is Moana Disney movie. The data was collected through the process of watching, pausing and interpreting all aspects of the movie that relate to the problem that was analyzed. The writer found that the image of women in the movie is imagined more active, strong, and brave to show the resistance of the stereotype and patriarchal system that used in literary work. However, the patriarchal system and stereotype were still found and existed in the movie throughsome aspects that appear after the feminist reading is done. It happened because of the influence of postmodernism which is the era of this movie is published as the result that applying feminist reading and postmodernism images of women in this movie still presented as inferior to men.